Are Romanian urban strategies planning for green?. Issue 1 (2nd January 2018) - Niță, Mihai-Razvan; Anghel, Ana-Maria; Bănescu, Cristina; Munteanu, Ana-Maria; Pesamosca, Sabina-Stella; Zețu, Mihuț; Popa, Ana-Maria
ABSTRACT: Faced with growing economic, social and environmental challenges, urban settlements increasingly use green areas in the search for achieving sustainability and resilience. The first step is typically the development of policies and strategies that include a significant green component. This present study analyses the development policies and strategies of 213 Romanian cities and how they approach urban green areas as well as applied means of development and management. We constructed a database with information extracted from these documents, applied descriptive statistical analysis and mapped the resulting distribution of indicators. Results indicated the preference of local urban administrations for simple objectives such as increasing or maintaining surfaces of green areas but lacking activities for achieving identified targets in improving the multifunctional benefits of green areas. We concluded that there are no differences in approaches using geographical settings or urban ranks. We determined that further research is required to connect policies and strategies with their subsequent implementation at a local level and the ensuing perceived effects. Results are critical in analysing the performance of local authorities in weak planning systems common in south-east European countries.